Recent Developments in Alcoholism 2005
DOI: 10.1007/0-306-48626-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Drinking among College Students

Abstract: For most of the American population, the college years represent the period of life associated with the highest levels of alcohol consumption and, most likely, the highest prevalence of alcohol use disorders during the lifespan (Grant, 1997). Recent research has focused increasingly on college student drinking. For example, a combined PsycINFO/Medline search of abstracts containing the words "alcohol or drink or drinking" shows a dramatic increase in the percentage of scholarly articles that contain the term "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 138 publications
(223 reference statements)
2
23
0
Order By: Relevance
“…drinking which increases one’s risk of alcohol-related problems; Friedmann, 2013) among college students is associated with a wealth of negative outcomes, such as elevated risk for substance abuse and dependence, damage to physical health, school dropout, and high-risk sexual behavior (see White & Hingson, 2014). There are numerous reasons for the increase in alcohol use and elevated risk for negative outcomes related to drinking; however, research has revealed that the situational context of attending college explains the increased drinking behaviors of college students above and beyond the effects of pre-college background characteristics such as personality and intelligence (Jackson, Sher, & Park, 2005; Slutske et al, 2004). Thus, some researchers have posited that certain social and environmental factors may actively promote or deter engagement in hazardous drinking among college students (Presley, Meilman, & Leichliter, 2002).…”
Section: Effects Of Romantic Relationships On Alcohol Usementioning
confidence: 99%
See 1 more Smart Citation
“…drinking which increases one’s risk of alcohol-related problems; Friedmann, 2013) among college students is associated with a wealth of negative outcomes, such as elevated risk for substance abuse and dependence, damage to physical health, school dropout, and high-risk sexual behavior (see White & Hingson, 2014). There are numerous reasons for the increase in alcohol use and elevated risk for negative outcomes related to drinking; however, research has revealed that the situational context of attending college explains the increased drinking behaviors of college students above and beyond the effects of pre-college background characteristics such as personality and intelligence (Jackson, Sher, & Park, 2005; Slutske et al, 2004). Thus, some researchers have posited that certain social and environmental factors may actively promote or deter engagement in hazardous drinking among college students (Presley, Meilman, & Leichliter, 2002).…”
Section: Effects Of Romantic Relationships On Alcohol Usementioning
confidence: 99%
“…Because hazardous drinking is associated with increased risk for engagement in a variety of dangerous behaviors such as driving while intoxicated, intimate partner violence, and illicit drug use (Jackson et al, 2005), partners in romantic relationships may endanger themselves and their partner when drinking heavily, which may in turn negatively impact the functioning of the relationship (Rodriguez, Neighbors, & Knee, 2013). Furthermore, concern over the negative consequences of heavy alcohol consumption and the well-being of the relationship may lead dyadic partners to experience more frequent negative exchanges (e.g., arguments) and negative affect toward their romantic partner (Walitzer, Dermen, Shyhalla, & Kubiak, 2013; Rodriguez, Øverup, & Neighbors, 2013).…”
Section: Effects Of Alcohol Use On Romantic Relationshipsmentioning
confidence: 99%
“…Large-scale surveys indicate that approximately 68% of all college students drank alcohol in the past month (Johnston, O'Malley, Bachman, & Schulenberg, 2006), and approximately 40% of all college students engage in heavy episodic drinking, defined as consumption of 5 or more drinks for men (4+ for women) in one drinking episode during the past 2 weeks (Wechsler, Dowdall, Davenport, & Rimm, 1995). Heavy episodic alcohol consumption in college students is related to numerous consequences, including academic difficulties, property damage, risky sexual activity, blackouts, alcohol poisoning, and death (Hingson et al, 2002; Jackson et al, 2005; Wechsler & Isaac, 1992). Recent reports indicate that college drinking has not decreased over the past decade (Johnston et al, 2006), and cross-sectional data evidenced a 16% increase in the proportion of students who engage in frequent heavy episodic alcohol use (≥3 in the past two weeks) between 1993 and 2001 (CASA, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Using two general population adult midwestern samples, one including same-gender female twins (Missouri Adolescent Female Twin Study [MOAFTS]; Heath et al, 1999) and the other including college-age male and female unrelated subjects ascertained initially through college attendance (College Drinking Study [CDS]; Jackson et al, 2005;Sher, 1991;Sher et al, 1991;Slutske et al, 2004), we investigated: (1) evidence for a unidimensional alcohol-consumption factor; (2) psychometric equivalence in the factorial structure of alcohol consumption across the MOAFTS and the CDS samples;…”
Section: Developing a Quantitative Measure Of Alcohol Consumption Formentioning
confidence: 99%